2014
DOI: 10.1016/j.jpainsymman.2013.12.241
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Opioid Use in Pediatric Inpatients Across Hospitals in the U.S.

Abstract: The substantial hospital-level variation in opioid use in pediatric inpatients suggests room for improvement in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 27 publications
2
31
0
1
Order By: Relevance
“…It is important to highlight that prevalence in this work (61%) is very similar to that reported in a study that only included onco-hematological pediatric patients (56.7%) [ 14 ] in spite of the study design and the used software being different, which can be explained by the high resemblance of the study populations in both works, since onco-hematological conditions are among the main causes the HIMFG provides care for [ 27 ]. Particularly, children admitted to EDs have critical medical conditions that make them more susceptible to the administration of multiple drugs, to complex treatment regimens, to long ED stays and to care by different specialist physicians for consultations [ 19 20 ]. There are more than 54 different softwares for DDIs assessment [ 28 ], but according to a systematic review that included articles of children and adults between 1976 and 2014, the most widely used are the Drug-Relax software from Micromedex® Healthcare Series, Drug Interactions Facts®, Lexi-Interact®, Pharmavista®, EpocratesRx®, MediQ® and Drug interaction checker® [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to highlight that prevalence in this work (61%) is very similar to that reported in a study that only included onco-hematological pediatric patients (56.7%) [ 14 ] in spite of the study design and the used software being different, which can be explained by the high resemblance of the study populations in both works, since onco-hematological conditions are among the main causes the HIMFG provides care for [ 27 ]. Particularly, children admitted to EDs have critical medical conditions that make them more susceptible to the administration of multiple drugs, to complex treatment regimens, to long ED stays and to care by different specialist physicians for consultations [ 19 20 ]. There are more than 54 different softwares for DDIs assessment [ 28 ], but according to a systematic review that included articles of children and adults between 1976 and 2014, the most widely used are the Drug-Relax software from Micromedex® Healthcare Series, Drug Interactions Facts®, Lexi-Interact®, Pharmavista®, EpocratesRx®, MediQ® and Drug interaction checker® [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of adult patients, different studies have been published reporting potential DDIs frequency, characteristics and risk factors [ 1 , 17 18 ], with two of these studies having been conducted in Mexico [ 1 , 18 ]. Among the studies that have reported potential DDIs frequency and characteristics, as well as their associated risk factors in the pediatric population, there wasn’t any identified that was carried out in the setting of an Emergency Department (ED), which is highly important, since especially children admitted to the ED have severe, life-threatening conditions, and this is a situation that makes them more susceptible to multiple drug administration, complex treatment regimens, prolonged ED stays and care by different specialist physicians for multiple consultations [ 19 20 ]. In addition, no publications were identified about studies conducted in Mexican children assessing potential DDIs, as well as their associated risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…More than 40% of hospitalized children and 90% of those undergoing surgery are exposed to opioids during their inpatient stay. 2 Unfortunately, in addition to being highly addictive, opioids are associated with significant side effects, including decreased gastrointestinal motility and respiratory depression. Furthermore, recent reports highlight an increased likelihood of long-term opioid use for children who receive an opioid prescription after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 . Morphine is still the drug of choice according to WHO for the treatment of acute or persistent severe pain in children with medical conditions in both oncological and non-oncological patients, with extensive scientific evidence supporting its prescription and monitoring 2,[25][26][27] . In light of the repeated studies showing deficits in the detection and management of pain in the hospital center studied, it is essential to achieve consensus for a better care of children and adolescents in pain 9,10 .…”
Section: Discussionmentioning
confidence: 99%